2021
DOI: 10.1186/s12984-021-00854-y
|View full text |Cite
|
Sign up to set email alerts
|

Walking stability in patients with benign paroxysmal positional vertigo: an objective assessment using wearable accelerometers and machine learning

Abstract: Background Benign paroxysmal positional vertigo (BPPV) is one of the most common peripheral vestibular disorders leading to balance difficulties and increased fall risks. This study aims to investigate the walking stability of BPPV patients in clinical settings and propose a machine-learning-based classification method for determining the severity of gait disturbances of BPPV. Methods Twenty-seven BPPV outpatients and twenty-seven healthy subjec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…VM patients also presented shorter step lengths. The results were identical to our previous study [33]. Remarkably, there is no signi cant difference in temporospatial parameters between VM and BPPV groups.…”
Section: Discussionsupporting
confidence: 90%
“…VM patients also presented shorter step lengths. The results were identical to our previous study [33]. Remarkably, there is no signi cant difference in temporospatial parameters between VM and BPPV groups.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, they are useful for implementing strategies to reduce the risk of falls which represents a major public health problem [50]. Recent reports suggest that IMUs, besides being useful in evaluating and to monitoring gait alterations in patients with neurodegenerative diseases such as Parkinson's disease [51][52][53], are useful for; patients with osteoarthritis [54], with benign paroxysmal positional vertigo, the most common peripheral vestibular disorder, leading to balance difficulties and increased fall risks [55] and walking disturbances in sarcopenic patients [56], they are also useful for gait event detection and analysis of gait alterations in patients with diabetes secondary to DPN [23,24,[27][28][29]31]. In spatiotemporal gait parameters recorded using a wearable sensor in patients with DPN, Kang et al showed that gait initiation steps and dynamic balance may be more sensitive than gait speed for detecting gait deterioration due to DPN [23], and Najafi et al demonstrated that gait alteration in patients with DPN is most pronounced while walking barefoot over longer distances [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, advanced classification procedures, such as machine learning-based algorithms, have relied on data captured by inertial sensors to differentiate clinical scores and to monitor a precision rehabilitation intervention [50] or to differentiate patients from healthy controls for determining the severity of gait disturbances [51]. In this last study, the gait symmetry was one of the relevant measures processed by the machine learning algorithms to determine a reliable severity score of gait disorders.…”
Section: Practical Implicationsmentioning
confidence: 99%